Addressing Serious Violent Misconduct in Prison: Examining an Alternative Form of Restrictive Housing - Meyers, Travis J. (International journal of offender therapy and comparative criminology, 2018)
A number of scholars, civil, and human rights activists have expressed concern about the negative impact restrictive housing may have on the physical and mental well-being of inmates. Rigorous, theoretically informed outcome evaluations, however, are virtually nonexistent. Guided by theory and existing empirical evidence, this study explores the future behavioral and mental health outcomes associated with completing an alternative approach to restrictive housing in the Arizona Department of Corrections. To explore program outcomes, we use paired-sample t tests to determine whether post-program behavior is significantly different from preprogram behavior. In addition, we use cross tabulations and independent samples t tests to identify relationships between individual-level inmate and program characteristics and program outcomes. Results from this study suggest that a more therapeutic restrictive status housing program has the potential to improve the future behavior of program graduates; however, future research is needed to build upon these findings.